2003
DOI: 10.1007/s00253-003-1372-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in an industrial wastewater bioreactor

Abstract: Industrial wastewater bioreactors are potentially important sources of novel biocatalysts. However, the microbial populations in these bioreactors are not well characterized. The microbial community in an industrial wastewater bioreactor was surveyed by extracting DNA from a sample of activated sludge, followed by PCR amplification and sequencing of cloned 16S rRNA genes. A total of 407 cloned 16S rRNA gene sequences were compared with 88 bacterial isolates cultured from the same sample of sludge using a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…It is suggested that by substituting activated sewage for the sewage-derived inoculum, little potential for biodegradation will be lost. In addition, we have shown that the sewage-derived bacterial consortium is composed of bacteria typically present in activated sewage (Bramucci and Nagarajan, 2000;Bramucci et al, 2003;Kavanaugh and Randall, 1994). Whilst activated sewage will contain organisms in addition to those isolated in this study, we have shown that the cultured consortium contains a range of bacteria representative of those found in the parent inoculum.…”
Section: Discussionmentioning
confidence: 86%
“…It is suggested that by substituting activated sewage for the sewage-derived inoculum, little potential for biodegradation will be lost. In addition, we have shown that the sewage-derived bacterial consortium is composed of bacteria typically present in activated sewage (Bramucci and Nagarajan, 2000;Bramucci et al, 2003;Kavanaugh and Randall, 1994). Whilst activated sewage will contain organisms in addition to those isolated in this study, we have shown that the cultured consortium contains a range of bacteria representative of those found in the parent inoculum.…”
Section: Discussionmentioning
confidence: 86%
“…The results of the present study show that the 16S rDNA clone libraries have high coverage, and can adequately represent the diversity of bacteria present in communities; 92% and 97% coverage was achieved for the two tanks, respectively (Table 4), and in other studies coverage has ranged from 28% to 93% (29). Bacterial diversity in wastewater treatment bioreactors has been examined in many studies (5,7,8,18,24). Findings from these studies suggest that the most frequently found types of bacteria are the β-proteobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Bramucci et al (5) surveyed bacterial diversity in an industrial wastewater bioreactor using 16S rDNA analysis and obtained 106 OTUs from 407 rDNA sequences. In a review of current research on microbial community composition and function in wastewater treatment plants, Wagner et al (29) noted that systems with low levels of functional redundancy (due to low levels of diversity for bacteria in certain functional groups) are more sensitive to failure than systems with high levels of functional redundancy (due to high levels of diversity in the same bacterial group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alphaproteobacteria was the dominant bacterium in activated sludge exposed to 620.5 mg/L of OTC, followed by Betaproteobacteria, Actinobacteria, and Firmicutes. Previous research reported that Betaproteobacteria was an important bacterial group in aerobic reactors (Bramucci et al 2003) and dominated OTC production wastewater treatment systems (Liu et al 2012), while Alphaproteobacteria was shown to dominate in 65 % of 86 investigated industrial wastewater treatment plants (Kragelund et al 2006). The increased presence of Actinobacteria and Firmicutes may relate to their ability to easily acquire antibiotic resistance.…”
Section: Discussionmentioning
confidence: 96%